Hyperbaric effects on cold stored whole blood following a military dive mission profile. (24th June 2022) - Scheiber, Christopher J.; Spencer, Chad M.; Neading, Richard D.; O'Connell, Michael P.; Becker, Casey F.; Scarborough, Tyler R.; Horsey, Jeremy D.; Perez, Joshua A.; Ochoa, Baron J.; Wilkinson, Michael A.; Bentley, Pasha; Seheult, Jansen N.; et al.
Abstract: Background: Whole blood (WB) is carried by special operations forces as part of a remote damage control resuscitation strategy. The effects of an underwater mission on the quality and coagulation profile of WB were simulated by exposure to hyperbaric pressures in a chamber. Methods: WB units collected in CPDA‐1 were exposed to three different combinations of hyperbaric pressure and duration of exposure: Group A 153.52 kPa (15.24 msw; 1.52 atm) for 4 h; n  = 9, Group B 506.63 kPa (50.29 msw; 5.00 atm) for 1 h; n  = 9, Group C 153.52 kPa (15.24 msw; 1.52 atm) for 1 h; n  = 7. The following parameters were measured on each unit: prothrombin time/international normalized ratio, activated partial thromboplastin time, thromboelastography and concentration determinations of platelets, lactate, fibrinogen, and lactate dehydrogenase. Each sample underwent baseline, prepressurization, immediate postpressurization, and 6 h postpressurization laboratory testing. Results: Six hours following hyperbaric exposure, the lactate concentration in group C was higher than prepressurization measurement and the platelet concentration in Group A was lower than prepressurization measurement. There were no changes in any of the other analyzed biochemical, coagulation and thromboelastogram parameters following exposure to hyperbaric stress. Discussion: These data suggest that pressurization of WB up to 5 atm did not impact parameters tested. Changes observed in lactate and platelet count need further study, as well as complementary testing of red blood cell integrity. Further investigation of the hyperbaric extremes is necessary to determine if there is a damage inducing pressure to which WB should not be exposed.